A Systematic Literature Review: The Influence of Work Environment and Work Motivation on Employee Performance - Hikmah, Diana Faiqotul; Hidayati, Fresty Nur; Adhimah, Himmatul; Fitroh, Alfiana Zakyatul; Fatimah, Nuzulul (CV. Proaksara Global Transeduka, 2024)
Work environment and job motivation are two important factors that have a significant effect on employee performance. This study aims to investigate the effect of work environment and job motivation on employee performance. This study found that the interaction between work environment and job motivation has a significant moderating effect on employee performance. Specifically, it was found that employees who experienced a positive work environment and were motivated by intrinsic factors performed better than those who did not. The implications of these findings suggest that organizations should prioritize creating a positive work environment and enhancing job motivation to improve employee performance. This research contributes to the pool of knowledge by providing insight into the complex relationship between work environment, job motivation and employee performance.